Analisa Pengaruh Putaran Spindel Terhadap Daya dan Efisiensi Pemotongan Pada Proses Pembubutan Baja St 60 Dengan Melakukan Perlakuan Panas - Marthina Mini; Bosta Sihombing; Tanwir Tanwir (Peneliti.net, 2022)
The manufacturing industry, especially in the turning process, where turning is a cutting process that uses machine tools to produce cylindrical shapes and can also be used to thread, drill and flatten rotating objects by cutting the rotating workpiece on the spindle using cutting tools (chisels ) that have a level of hardness above the formed workpiece. The results obtained from this study are to obtain the value of the power and efficiency of the material without heat treatment, the value of power is 0.081154 kw at 290 rpm, 0.103542 kw at 370 rpm, 0.128727 kw at 460 rpm. The efficiency value is 0.000054 (%) at 290 rpm 0.00006902 (%) at 370 rpm 0.0000858 (%) at 460 rpm rotation. For heat-treated materials, the power value is 0.081154 kw at 290 rpm, 0.103542 kw at 370 rpm, 0.128727 kw at 460 rpm. The efficiency value is 0.0000541 (%) at 290 rpm 0.000069028 (%) at 370 rpm, 0.0000858 (%) at 460 rotation for 60 mm infeed length